Challenges of Achieving Sustainable Development Goal 7 From the Perspectives of Access to Modern Cooking Energy in Developing Countries - Tucho, Gudina Terefe; Kumsa, Diribe Makonene (Frontiers in Energy Research, 2020)
Sustainable development goal 7 (SDG 7) focuses on ensuring access to affordable, reliable, sustainable, and modern energy for all by 2030. This goal has a lot of synergies and associations with the rest of SDGs and in particular to goals 1,3,4,5 and 15. Nevertheless, achieving this goal with the provisions of access to affordable and sustainable modern cooking energy will be very challenging when past failed programs are considered. The challenges could be paramount in Sub-Saharan Africa, where still the majority of the population does not have access to improved cooking energy services. The low achievement attributes to the interrelated deep-rooted socio-economic, cultural, and technical factors. Without breaking these barriers and having an integrated economic and social policy, achieving this goal remains ambitious without success. Hence, continuing with business as usual with the existing policy may not work. Besides, there can be unforeseen circumstances like the COVID-19 pandemic with a lot of health, economic, and social crises that also needs to take into account. In addition to having a better policy to ease the socio-cultural issues, there should be the availability of sufficient economic incentives to invest in energy projects and support the households. Otherwise, achieving this goal may remain ambitious by leaving over 70% of the people in Sub-Saharan Africa dependent on traditional use of biomass energy by 2030.